TEST OF AMYLASE INHIBITION ACTIVITY OF METHANOL EXTRACT SINGKIL LEAF (Premna cordifolia Roxb.) - Anggriani, Yusnia Wati; Astuti, Winni; Marliana, Eva (PROSIDING SEMINAR KIMIA, 2023)
Singkil (Premna cordifolia Roxb.) is a plant that is widely found un Kalimantan. The people of Kalimantan are often used singkil leaf by as traditional medicine are believed to have medicinal properties as a cure for intestinal worms, colds, and antidiabetic. In this research, it used phytochemical screening and inhibition activity amylase test on singkil’s methanol extract. The objective of this study was to determine in-vitro enzyme amilase inhibition activity against sampel by DNS method. The result of this research was phytochemical screening in singkil’s methanol extract contains alkaloids, flavonoids, saponins and phenolics. Singkil leaf methanol extract at a concentration of 10 µg/mL can inhibit the activity of the amylase enzyme with an inhibition value of 60,93 %. Acarbose used as a positive control in this study showed activity against the amylase of 44,79 %. Amylase inhibition activity of methanol extract was higher than acarbose, the singkil leaf methanol extract has the potential as an antidiabetic drug. Keywords: Premna cordifolia Roxb., Amylase inhibition, Secondary Metabolites.